The consequences of the Fisrt Worldf War on the Societe Musicale Independante - SMI - Longo Benedetti, Danieli Veronica [UNESP] (Univ Federal Goias, 2018)
This article - part of a postdoctoral research - intends, through the analyses of the documents from Societe Musicale Independante - SMI (Programs SMI, Bibliotheque nationale de France, BnF - Musique), to reveal the accomplishments of musical concerts during the World War I (1914-1918), as well as a consideration around the compositions selected by the committee of the SMI, throughout the war.
Keywords: Musicology; Societe Musicale Independante; Music association; Composers; World War One